Indocyanine Green and Fluorescein Filters Reveal Dye Staining before Clinical Development of Hives. Issue 1 (2017) - La Spina, Carlo; Broganelli, Paolo; La Selva, Roberta; Demasi, Christian Luigi; Querques, Giuseppe
Purpose: During retinal angiography a fluorescein-induced allergic reaction is rare but possible. Methods: We report a single retrospective clinical case. Results: During retinal angiography on a 75-year-old man, an unexpected allergic reaction to fluorescein (FL) dye occurred. At the beginning of the exam, we erroneously took some filtered shots of the patient's face. We noticed that the pictures of the patient's skin using the FL and indocyanine green filters revealed dye accumulation before the clinical appearance of hives. Conclusions: Taking filtered shots of a patient's face could be an original method to promptly detect and easily document allergic hives, by simply using an angiographic device.